UNO Studio's Digital Reservation and Payment Process System Uses a Prototype Approach and Midtrans Payment Integration - Fariansyah Arkanda, Rayangga; Suharso, Wildan (INOVTEK Polbeng - Seri Informatika, 2026)
Digital transformation is crucial for small and medium-sized enterprises (SMEs) to remain competitive and more efficient in the modern era. This research focuses on the digitalization process of UNO Studio, a company that provides photography and studio rental services. Currently, UNO Studio faces operational challenges due to its manual reservation system. This manual method can lead to delays, scheduling errors, and inefficiencies. Therefore, this research aims to upgrade UNO Studio's reservation system to a web-based system fully integrated with a digital payment system. The method used is a prototype approach applied in the software reengineering process. The system was built using HTML, CSS, and JavaScript, with Supabase as the data manager and Midtrans to integrate payments automatically and in real time. Black-box testing results show that all key system features run smoothly without errors. Furthermore, User Acceptance Testing (UAT) results indicate a user satisfaction rate of 88.70%, considered excellent. Overall, this system successfully automates the entire reservation and payment process, improving operational efficiency and service accuracy and enhancing the quality of customer service through secure and easy-to-use digital integration.